Pengaruh Pemberdayaan dan Kepercayaan Terhadap Loyalitas Guru SMA Negeri Kota Depok - Asep Zainudin; Rugaiyah -; Elais Retnowati (Peneliti.net, 2018)
This study aims to contribute to the development of education management and enrich conceptual studies related to create quality education through increase for teacher loyalty and discover loyalty factor there is empowerment and trust This research is a quantitative research with survey method and uses path analysis. The population in this study were teachers in the state high school in Depok. The data obtained from the questionnaire given to 100 teachers is about impact of loyalty, empowerment and teacher trust with their school. From the data calculated and analyse there are three research result; empowerment of teacher has a positive effect on teacher loyalty, then the trust of teacher has a positive effect on teacher loyalty, and the last is empowering teachers to have a positive effect on teacher's trust.